2020
DOI: 10.1002/ehf2.12742
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictors of all‐cause mortality in patients presenting to specialist heart failure clinic with raised NT‐proBNP and no heart failure

Abstract: Aims Clinical outcomes for patients suspected of having heart failure (HF) who do not meet the diagnostic criteria of any type of HF by echocardiography remain unknown. The aim of this study was to investigate the clinical predictors of all-cause mortality in patients with suspected HF, a raised N-terminal pro-b-type natriuretic peptide (NTproBNP) and who do not meet the diagnostic criteria of any type of HF by echocardiography. Methods and results Relevant data were taken from the Sheffield HEArt Failure (SHE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
(33 reference statements)
0
8
1
Order By: Relevance
“…On univariate analysis, beta-blockers showed an association with survival, however that apparent association disappeared with multivariate Cox proportional-hazards regression that adjusted for all variables found in our previous report to be associated with mortality. 8 None of the other cardiovascular therapeutic agents (diuretics, ACEi, MRA or digoxin) were shown to have any association with these patients’ survival.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…On univariate analysis, beta-blockers showed an association with survival, however that apparent association disappeared with multivariate Cox proportional-hazards regression that adjusted for all variables found in our previous report to be associated with mortality. 8 None of the other cardiovascular therapeutic agents (diuretics, ACEi, MRA or digoxin) were shown to have any association with these patients’ survival.…”
Section: Discussionmentioning
confidence: 93%
“…However, using multivariate Cox proportional-hazards regression to adjust for all variables associated with mortality, 8 the influence of beta-blockers became non-significant (HR 0.96; 95% CI: 0.85 to 1.1, p=0.49) ( table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have published the clinical predictors of mortality in this group of people. 11 The patients diagnosed with HF had a significantly higher mortality rate of 11.5 (95% CI 11 to 12.2) per 100PY.…”
Section: Discussionmentioning
confidence: 93%
“…We prospectively entered all patients referred to the HF clinic into the SHEAF registry. 11 We excluded the few patients before 2013 whose entry into the diagnostic algorithm was through a history of MI. We observed that GPs tended to test the NT-proBNP even when there was a history of MI.…”
Section: Discussionmentioning
confidence: 99%